Fundamental insights into the alloy miscibility and surface chemistry of metal nanoclusters - Anderson, Ian David, author; Ackerson, Christopher J., advisor; Shores, Matthew P., committee member; Van Orden, Alan, committee member; Prenni, Jessica E., committee member (Colorado State University. Libraries, 2022)
The fascinating and varied properties of metals have captured people's imaginations long before the advent of modern chemistry. Basic metallurgy, dating as far back as the fourth millennium BC, remains one of the most consequential processes in human history. Today we enjoy an effective mastery over metals in their continuous bulk state, complete with alloy phase diagrams which describe properties as a function of temperature and percent composition. The coordination chemistry of single-metal complexes is similarly well-studied, initiated by the pioneering work of Alfred Werner in 1893. Size-dependent properties found at these two extremes (continuous bulk versus discrete molecular) have facilitated a myriad of applications in nearly every aspect of society through the development of unique materials. Between bulk metals and coordination complexes exists a new and rapidly growing area of chemistry concerned with clusters containing several to hundreds of metal atoms. Although there are commonalities shared with both molecular and bulk systems, these clusters also exhibit notable behavioral differences which can often not be explained through simple classical interpretations. The challenge of working with these species has been considerably eased within the past fifteen years from advancements in synthesis and characterization, in particular for monolayer-protected clusters (MPCs) of gold. These MPCs can be synthesized to precise monodispersity and are therefore defined by a molecular formula instead of the more general average size and dispersity used to define larger (typically > 3 nm) colloidal nanoparticles. Minor adjustments to the nuclearity, metal atom identity, or surface chemistry of gold MPCs have been shown to induce extensive changes in their observed properties and overall stability. Complete regiochemical control over both the metal core composition and surface ligand environment is therefore of immediate interest. This goal is especially important for potential applications in catalysis, electronics, biolabeling, energy conversion/storage, and theranostics. The work described herein covers two overarching themes: i) examining the alloying ability of gold MPCs with various late transition metals, and ii) an investigation of MPC surface chemistry through the introduction of multidentate ligands. Synthesis and analysis of the classically-immiscible rhodium-gold system using Au25(SR)18 as a template offers a fresh perspective of alloy gold MPCs containing metals with an open d-shell, alongside an updated framework for understanding MPC stability. Acetylide-for-thiolate, thiolate-for-acetylide, and intercluster exchange between acetylide- and thiolate-protected gold MPCs reveal lability which cannot be adequately rationalized through traditional MPC ligand exchange arguments. The first example of a thiolated gold MPC co-protected by several oxygen-containing diglyme ligands is described, which exhibits enhanced thermal stability as a result of the robust gold-diglyme, thiolate-diglyme, and diglyme-diglyme interactions. A straightforward synthetic pathway to fully dithiolate-protected gold MPCs is also described, as well as a post-synthetic ligand exchange study showcasing their resistance against incoming monodentate thiol exchange. Lastly we provide a series of vignettes detailing our efforts towards the synthesis of various MPCs using metals such as osmium, iridium, and bismuth. Overall these studies afford fundamental advancements in the understanding of soluble, air-stable metal nanoclusters and open up new opportunities for their applications.
Keywords: clusters; gold; thiolates; glymes; acetylides; rhodium